The Effect Of Domestic Investment And Foreign Direct Investment On The Increase Labor Absorption In Indonesia During 2015–2024: An Islamic Economics Perspective - Lora Ayu Agustina; Muhammad Iqbal; M. Yusuf Bahtiar (Journal of Contemporary Applied Islamic Philanthropy, 2026)
Purpose: This study aims to analyze the effect of domestic investment and foreign direct investment on employment absorption in Indonesia during the 2015–2024 period from the perspective of Islamic economics. Methodology: The study employs a quantitative approach using panel data analysis. The data were obtained from Statistics Indonesia (BPS) and the Indonesia Investment Coordinating Board (BKPM). Findings: The results indicate that both domestic investment and foreign direct investment have a significant effect on employment absorption, both partially and simultaneously. The coefficient of determination of 34.1% suggests that variations in employment absorption can be explained by these two variables, while the remaining 65.9% is influenced by other factors outside the scope of this study. From the perspective of Islamic economics, investment is not solely intended to generate profits but must also uphold the principles of justice, public welfare (maslahah), and social well-being through job creation and the reduction of social inequality. This study is expected to serve as a reference for formulating investment policies that prioritize labor-intensive sectors to increase employment absorption, reduce unemployment, and promote a more inclusive and equitable distribution of welfare in Indonesia.